PENETAPAN TARIF SEWA KAMAR PADA HOTEL PANGERAN BEACH PADANG - Nadila Octaviani Putri; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The city of Padang stretches from north to south with a beach and a row of Bukit Barisan, the combination of the two locations provides an attractive and beautiful natural beauty for the city of Padang, thus encouraging the West Sumatra provincial government to provide various facilities and infrastructure such as hotels. Thanks to the large number of hotels, the hotel management competes with each other in providing good service to their customers. In this case, Prince Beach Padang Hotel carefully considers in setting room rental rates so that the price set does not cause harm to the company. The purpose of this study was to determine the setting of room prices at the Pangeran Beach Padang hotel. Based on the method used in this study, namely descriptive qualitative method to analyze the problems that the authors collected through observation, interviews and documentation with the management of the Prince Beach Padang hotel. Based on the data analysis carried out, the selection of strategies and methods must adjust the existing market conditions because this is very influential in determining the price of the Prince Beach Padang hotel. Keywords: Price, Strategy, Method, Hotel